(untitled) (Research, Society and Development, 2023)
This article addresses educational policies and teacher training in higher education in Guinea-Bissau. Its central objective is to understand and analyze educational policies and teacher training in Guinean higher education. In the construction of this article, we present the theoretical precepts that underlie teacher training processes in higher education in that country. The methodology of this work was carried out through a narrative review on the subject based on the authors: Mainardes; Gatti; Mendes; Ball; Passone; Souza among others. The result of this work shows how important educational policies and teacher training are in which one can consider the need to promote improvements in the teacher training process in undergraduate courses and in higher education in Guinea-Bissau. It is concluded that, in relation to the educational sector of Guinea-Bissau, there are gaps and a need to expand and offer teacher training schools, as well as the application of more financial resources in the country’s education and that the partnership with other countries and international bodies has contributed to guarantee the training of Guinean teachers.